Small Atom Doping: A Synergistic Strategy to Reduce SnZn Recombination Center Concentration in Cu2ZnSnSe4. Issue 11 (8th November 2022) - Jimenez-Arguijo, Alex; Navarro Güell, Alejandro; Sanchez, Yudania; Malerba, Claudia; Valentini, Matteo; Becker, Pascal; Choubrac, Leo; Unold, Thomas; Jehl Li-Kao, Zacharie; Giraldo, Sergio; Saucedo, Edgardo
Abstract : Small Atom Doping In article number 2200580, Alex Jimenez‐Arguijo, Edgardo Saucedo, and co‐workers implemented transient doping with H and Li during the synthesis of kesterite Cu2 ZnSnSe4 . This strategy allows engineering the defect structure of kesterite towards photovoltaic applications, as well as improving the thin film morphology, demonstrating the potential of this strategy to overcome the fundamental limitations of kesterite and other thin film chalcogenide compounds.